2011
DOI: 10.1136/vr.d2393
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial susceptibility of Pseudomonas aeruginosa isolates from dogs with otitis externa

Abstract: Pseudomonas aeruginosa is a common cause of otitis externa in dogs, and treatment of these infections is becoming problematic because of the increasing number of multiresistant strains. The aim of the present study was to compare the in vitro activities of cefepime, ceftazidime, enrofloxacin, ciprofloxacin, gentamicin and ticarcillin/clavulanic acid against 104 strains of P aeruginosa isolated from dogs with otitis externa. Antimicrobial susceptibility and minimum inhibitory concentrations, in µg/ml, were eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
50
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 18 publications
9
50
0
3
Order By: Relevance
“…These findings were expected and are in agreement with the results of other studies (RIDDLE et al, 2000;TEJEDOR et al, 2003;MEKIĆ et al, 2011).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…These findings were expected and are in agreement with the results of other studies (RIDDLE et al, 2000;TEJEDOR et al, 2003;MEKIĆ et al, 2011).…”
Section: Discussionsupporting
confidence: 83%
“…Compared to this study, a lower susceptibility rate was reported in Croatia a few years ago (MEKIĆ et al, 2011) with one (1.1%) strain susceptible to enrofloxacin. In that study susceptibility testing was performed by Etest ® .…”
Section: Discussionmentioning
confidence: 45%
See 1 more Smart Citation
“…However, panaminoglycoside resistance e.g., gentamicin, spectinomycin, streptomycin and amikacin has been increasingly reported in the P. aeruginosa dog and cat isolates [18,19,23]. Such resistance has been clarified to be predominantly due to a poorly understood mechanism namely "impermeability resistance" as a consequence of diminished drug uptake and/or accumulation [21,31].…”
mentioning
confidence: 99%
“…However, there is likely a much larger impact from the widespread dissemination of other multidrug-resistant pathogens that are more common causes of infection in pets, such as meticillin-resistant Staphylococcus pseudintermedius (Perreten and others 2010) and, as reported by Mekić and others (2011) in this week's issue of Veterinary Record , multidrug resistant Pseudomonas species.…”
mentioning
confidence: 99%